2018
DOI: 10.1002/bdr2.1347
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of microcephaly and selected brain anomalies in Argentina: Relationship with Zika virus and other congenital infections

Abstract: The prevalence of microcephaly was significantly higher when compared with the previous period. The system had the capacity to detect five cases with congenital ZIKV syndrome in a country with limited viral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…Cross-reactivity in diagnostic assays between SLEV and other flaviviruses complicates differential diagnosis (6). This is particularly challenging in Argentina where there are dengue virus (DENV) outbreaks frequently, history of jungle yellow fever, and Zika virus (ZIKV) activity was demonstrated and YFV vaccination is common in some regions (7)(8)(9)(10) Regarding the specific antiviral response pattern against SLEV, IgM antibodies persistence has been detected in some patients showing that the presence of IgM might not be indicative of acute infection (11,12). Spinsanti et al have shown that in 57% of the samples studied IgM antibodies persisted after a year of the infection.…”
Section: Manuscriptmentioning
confidence: 99%
“…Cross-reactivity in diagnostic assays between SLEV and other flaviviruses complicates differential diagnosis (6). This is particularly challenging in Argentina where there are dengue virus (DENV) outbreaks frequently, history of jungle yellow fever, and Zika virus (ZIKV) activity was demonstrated and YFV vaccination is common in some regions (7)(8)(9)(10) Regarding the specific antiviral response pattern against SLEV, IgM antibodies persistence has been detected in some patients showing that the presence of IgM might not be indicative of acute infection (11,12). Spinsanti et al have shown that in 57% of the samples studied IgM antibodies persisted after a year of the infection.…”
Section: Manuscriptmentioning
confidence: 99%
“…Additionally, if we are studying a population specifically because we suspect an excess number of cases (as in the setting of Zika epidemics), we would expect to observe an even greater prevalence using such a definition. However, several recent surveillance studies from South America that cited these definitions have reported a far lower prevalence of microcephaly, with estimates varying between 1 and 12 in 10 000 children (from 0.01% to 0.12%) . Of these four studies, two specify that additional clinical, laboratory, or radiological criteria are required for case confirmation though these criteria are not specified .…”
Section: Introductionmentioning
confidence: 99%
“…Of these four studies, two specify that additional clinical, laboratory, or radiological criteria are required for case confirmation though these criteria are not specified . In the two remaining studies, there is no further explanation of the criteria used to diagnose microcephaly beyond the head circumference cut‐off . Surveillance studies conducted throughout the US during a similar time period have emphasised the need for additional neuroimaging and clinical diagnosis, but the exact types of clinical evaluation were not always specified or consistent across these studies …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations